Keputusan Etis Konsultan Pajak: Pentingnya Tanggung Jawab Sosial dan Machiavellianisme - Yesheca Gracia Christian; Yulius Kurnia Susanto (Universitas Prasetiya Mulya, 2021)
This research objective is to get evidence about the effect of perception of the importance of ethical and social responsibility, Machiavellianism, ethical reasoning, idealism, experience, and professional commitment to ethical decision-making of tax consultants. Data were obtained from the questionnaire. This research used the convenience sampling method. This study used 60 tax consultants as the study samples in DKI Jakarta, and the data were analyzed using multiple regression analysis. This research showed that the perception of the importance of ethical and social responsibility, Machiavellianism, and ethical reasoning affects the ethical decision-making of tax consultants. The results showed that tax consultants with a high perception of the importance of ethical and social responsibility and ethical reasoning and low perception of Machiavellianism support that tax consultants conduct ethical decision-making. Meanwhile, idealism, experience, and professional commitment do not affect tax consultants' ethical decision-making. The implications of this research are for tax consultants to maintain the perception of the importance of ethics and social responsibility, and ethical considerations to make ethical decisions. The limitation of this study is that it uses respondents' perceptions of questions related to all variables. This finding shows that there is still a subjective element of the respondents.